EFFECTIVENESS MODEL OF MUNCAR PORT PUBLIC SERVICES: ANALYSIS OF PUBLIC SERVICE QUALITY - Tito Mariano Yesayabela; Aditya Tri Agustian; Ayu Wulandari Gunawan; Lunariana Lubis; Anma Sofyan Wahyudi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
Bureaucratic fragmentation in licensing poses a direct threat to the livelihoods of vulnerable fishermen at Muncar Port. A One-Stop Integrated Service (PTSP) model was implemented in 2021 to resolve this fragmentation. This study aims to quantitatively measure the effectiveness of this PTSP model from the user (fishermen) perspective. The research employed a quantitative descriptive design, surveying 30 fishermen selected via accidental sampling. Data was collected using a questionnaire structured on the five SERVQUAL dimensions (Tangibles, Reliability, Responsiveness, Assurance, Empathy) and analyzed using descriptive statistics. The findings indicate the model is only